Mechanism of professional adaptation of remote workers - O. Y. EMELYANOVA; V.S. SAMSONOV; I.V. SHERSHEN; M.A. KRAVETS (The journal of contemporary issues in business and government, 2020)
Abstract: The article discusses the issue of adaptation of teleworkers to the conditions of professional activity, which is relevant in modern labor policy. A range of problems that hinder adaptation and act as a trigger for the escalation of personal psychological problems are outlined: a symbiosis of business and household responsibilities in a home office, difficulties in organizing communications, etc. The internal and external "levers" of influence on the adaptation process of a remote worker are revealed. Particular attention is focused on institutions (educational organizations, government agencies to support vulnerable categories of the population and employment services, non-profit organizations and organizations in the business sector) that are able to accompany and optimize the adaptation mechanism for remote workers in organizational and methodological terms.